2003
DOI: 10.1007/s11920-003-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Children’s mental health after disasters: The impact of the world trade center attack

Abstract: This paper summarizes the results of systematic studies published in peer-reviewed journals from 1999 to 2002 addressing post-traumatic stress reactions in children after mass disasters. Children's post-traumatic reactions are considered in five different contexts--natural disasters, large-scale human-induced accidents, spree shootings, war, and terrorism. Association of these reactions with gender and age, as well as longitudinal course, is addressed. Other post-traumatic reactions in children after a mass di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 53 publications
0
46
0
4
Order By: Relevance
“…Prevalence of psychiatric disorders in one study was two to three times as high in New York city school students as it was in closeby urban and suburban school students tested a year earlier (Hoven et al, 2003), though it is possible that Manhattan rates were higher before the bombings as well.…”
Section: Exposure To Distant Traumamentioning
confidence: 87%
“…Prevalence of psychiatric disorders in one study was two to three times as high in New York city school students as it was in closeby urban and suburban school students tested a year earlier (Hoven et al, 2003), though it is possible that Manhattan rates were higher before the bombings as well.…”
Section: Exposure To Distant Traumamentioning
confidence: 87%
“…A disaster or mass-casualty incident can have significant psychological effects on children, including anxiety, feelings of loss of control, depression, sleep disturbance, developmental regression, and symptoms of posttraumatic stress disorder. 36,37 Provision of appropriate counseling and referral is important in the return toward normalcy for some children after a disaster. In the present study, 75% of the superintendents surveyed reported that their plan included provision for either in-school counseling or referral of troubled students to local mental health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the prevalence rate for PTSD in children has varied considerably (Hoven et al, 2003). Consequently, it is difficult to estimate the rates of PTSD given widespread differences across studies in the assessment measures, ages of the youth assessed, timing of the postdisaster assessment, type and severity of the disaster, and sample selection procedures, among other issues .…”
Section: Ptsdmentioning
confidence: 99%